2010
DOI: 10.1119/1.3356876
|View full text |Cite
|
Sign up to set email alerts
|

Orientation change of a two-dimensional articulated figure of zero angular momentum

Abstract: Simple, simpler, simplest: Spontaneous pattern formation in a commonplace system Am. J. Phys. 80, 578 (2012) Determination of contact angle from the maximum height of enlarged drops on solid surfaces Am. J. Phys. 80, 284 (2012) Aerodynamics in the classroom and at the ball park Am. J. Phys. 80, 289 (2012) The added mass of a spherical projectile Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Walker [6]) and it has been studied by Kaufman [7] who, however, argues that this mechanism is not sufficient to explain the 180°turn. Other studies of this general type can be found in [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Walker [6]) and it has been studied by Kaufman [7] who, however, argues that this mechanism is not sufficient to explain the 180°turn. Other studies of this general type can be found in [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%